Naturally occurring neem gum: An unprecedented green resource for bioelectrochemical flexible energy storage device. (8th November 2019) - Dhar, Abhishek; Kumar, Nadavala Siva; Khimani, Mehul; Al‐Fatesh, Ahmed S.; Ibrahim, Ahmed A.; Fakeeha, Anish H.; Bhadja, Poonam; Vekariya, Rohit L.
Summary: Naturally available neem tree gum consisting of bioelectrolyte and bioelectrode was fabricated for flexible energy storage device. Structural morphology, thermal stability, porosity and surface area of as prepared bioelectrode were characterized thoroughly by using scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and Brunauer–Emmett–Teller (BET) isotherm respectively. The bioelectrolyte conductivity was optimized under various concentrations of lithium ion salts and temperatures through electrochemical impedance spectroscopy (EIS). A flexible supercapacitor (SCs) was fabricated by using bioelectrodes and electrolyte and tested for its electrochemical properties. The supercapacitor displayed specific capacitance of 640 Fg ‐1 and 200 Fg ‐1 at a current density 0.5 Ag ‐1 and 1.0 V operating potential window. The energy device has also demonstrated large operational window (2.0 V) and shown 102 Fg ‐1 at a current density of 1.0 Ag ‐1 . The novelty of the present work lies in the simplified, cost‐effective procedure for preparation of biomaterials, their remarkably high stability under strong mechanical bent and long‐term charging‐discharging cycles of the fabricated device.